Resilience of Rural Communities Facing Global Challenges - Yusriadi, Yusriadi; Andi Kaslin (Journal of Indonesian Scholars for Social Research, 2025)
Rural communities globally face interconnected challenges, from climate change and natural disasters to economic shocks and pandemics, increasing their vulnerability. Effective adaptation and resilience strategies are crucial. This systematic review identifies, analyzes, and synthesizes these strategies employed by rural communities facing global challenges. Following PRISMA guidelines, the review will search Scopus, Web of Science, AGRICOLA, and JSTOR for peer-reviewed English articles (2010-2024). Keywords include "rural community resilience," "climate change adaptation," "food security," "agricultural resilience," "disaster risk reduction," "social capital," and "livelihood diversification." Inclusion criteria are empirical research articles specifically addressing adaptation and resilience strategies in developing country rural communities facing global challenges, focusing on climate change, economic crises, and natural disasters. A two-stage selection process (title/abstract, then full-text review) will be used. Quality assessment will utilize appropriate tools for quantitative and qualitative studies. Data from selected articles will be extracted and thematically analyzed using a deductive approach, identifying common themes related to adaptive capacity, livelihood diversification, social capital, local knowledge, and government policy roles. The review anticipates identifying effective adaptation and resilience strategy patterns, determining key influencing factors, comparing intervention effectiveness, and highlighting research gaps. This review provides valuable information for policymakers, researchers, NGOs, and stakeholders working to enhance rural community resilience.